Academicians’ Perception of the Implementation of Anti-Corruption Character Education in Higher Education - Bantam, Dian Juliarti; Nur Zhafarina, Adlia (Journal An-Nafs: Kajian Penelitian Psikologi, 2022)
The study aimed to analyze the implementation of anti-corruption character education in tertiary institutions. The participants of this study were 1218 academicians consisting of students (1118 people), lecturers (75 people), and education staff (25 people) in the universities across Yogyakarta. Data collection was conducted online for approximately 3 months via Google form, using the Anti-Corruption Character Building Questionnaire (ACCBQ) scale. Based on the collected data, the coefficient of Cronbach Alpha reliability was 0.948. The data analysis used descriptive data analysis divided into five categories, including very low, low, medium, high, and very high. The results of the study generally indicated that there were 5 (0.4%) participants who were in the very low category, 22 (1.8%) participants who were in the low category, 81 (6.7%) participants who were in the moderate category, 629 (51.6%) participants in the high category, and 481 (39.5%) participants in the very high category. This means that the academic community perceived the implementation of anti-corruption character education in universities in Yogyakarta as the 'high' category (51.6%; N = 1218, Âµ = 4.28, Ïƒ = 0.702). Further analysis was also carried out using nonparametric statistical analysis of the Kruskal Wallis test showing that there were significant differences between cognitive, affective, and psychomotor aspects (p <0.05). The results also showed that there were varying perceptions among the academic community regarding anti-corruption character education. This was influenced by individual characteristics, including gender (male and female), higher education classification (private and state universities), study program clusters (humanities and social sciences and natural sciences and technology), and classification of academicians (lecturers, education staff, and students).